1996
DOI: 10.1038/bjc.1996.187
|View full text |Cite
|
Sign up to set email alerts
|

Tirapazamine-induced DNA damage measured using the comet assay correlates with cytotoxicity towards hypoxic tumour cells in vitro

Abstract: Summary Tirapazamine (SR 4233), a bioreductive drug selectively toxic towards hypoxic cells, is presently in phase II clinical trials. Since it would not be expected that all tumours would respond equally to the drug, we are exploring ways of predicting the response of individual tumours. In this study we have tested whether the comet assay, which measures DNA damage in individual cells, can provide a simple, surrogate end point for cell killing by tirapazamine. We examined the relationship between the cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 34 publications
0
60
0
Order By: Relevance
“…It is of interest to note that SR4317 is not metabolized when incubated with breast cancer cell lysates in hypoxia (EC Chinjie and H Barham, unpublished data) and that SR4330, the four-electron reduced product was not detected in the metabolism studies reported here or by Patterson et al (1995) or Siim et al (1996). SR4317 can also be formed by direct two-electron reduction of tirapazamine by DT-diaphorase (Riley and Workman, 1992), thus bypassing the tirapazamine radical.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is of interest to note that SR4317 is not metabolized when incubated with breast cancer cell lysates in hypoxia (EC Chinjie and H Barham, unpublished data) and that SR4330, the four-electron reduced product was not detected in the metabolism studies reported here or by Patterson et al (1995) or Siim et al (1996). SR4317 can also be formed by direct two-electron reduction of tirapazamine by DT-diaphorase (Riley and Workman, 1992), thus bypassing the tirapazamine radical.…”
Section: Discussionmentioning
confidence: 96%
“…This strongly implicates P450 reductase-driven activation of tirapazamine to its one-electron reduced radical as an important contributory factor to the hypoxic toxicity of this drug, and this is consistent with our previous studies using a range of breast cancer cell lines. In contrast, Siim et al (1996) have exam-ined the hypoxic metabolism of tirapazamine by a variety of human and rodent cell lines of diverse histological type and showed that SR4317 formation correlated poorly with toxicity, whereas loss of tirapazamine was significantly related to drug potency. However, the reductive metabolic routes that could result in loss of tirapazamine and generate a radical (to give DNA strand breaks and toxicity) without subsequent production of SR4317…”
Section: Discussionmentioning
confidence: 99%
“…Both sets of data are compatible with the hypothesis that NOSII activity is involved with the hypoxic activation of TPZ. It has been suggested that the mechanisms implicated in aerobic and hypoxic cytotoxicity are distinct, and a wealth of experimental data indicate that DNA is an important cellular target for TPZ (Biedermann et al, 1991;Siim et al, 1996;Peters et al, 2001). However, the exact nature of the chemical species responsible for TPZ-mediated strand cleavage remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization-reionization mass spectrometry (NR MS) [10] is a method allowing the generation of unusual and previously unknown neutrals in the gas phase by neutralization of their (stable) positively charged counterparts. Although the sequence of events leading to activated drug (2) in the NR MS experiment is distinct from those that take place inside cells, this experiment offers a unique method for the generation of the activated form of tirapazamine in the gas phase.…”
Section: Neutralization-reionization Experiments With M ϩ⅐ and [M ϩ Hmentioning
confidence: 99%